2008
DOI: 10.1007/s00417-007-0722-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects in acute optic neuritis - distribution of different types of defect pattern, assessed with threshold-related supraliminal perimetry, ensuring high spatial resolution

Abstract: Central scotomas and retinal nerve fibre bundle defects are the most common VFDs in acute ON. Small central and paracentral scotomas that most probably would have been missed by automated thresholding perimetry with its relatively coarse grid could be detected by threshold-related, slightly supraliminal strategy. Of the fellow eyes in clinically apparent monocular optic neuritis, 35% present with visual field defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…In recent studies published by Nevalainen et al 15 and Fang et al, 16 a similar visual field pattern was demonstrated. Central scotomas and nerve fiber bundle defects were reported as the most common, with a slight “condensation” of visual loss between the center and the blind spot of the visual field.…”
Section: Commentsupporting
confidence: 62%
“…In recent studies published by Nevalainen et al 15 and Fang et al, 16 a similar visual field pattern was demonstrated. Central scotomas and nerve fiber bundle defects were reported as the most common, with a slight “condensation” of visual loss between the center and the blind spot of the visual field.…”
Section: Commentsupporting
confidence: 62%
“…The latter two eyes had very poor visual detection of hand movements and failed to perform GVF initially. Two eyes that showed initial altitudinal defects, which is more common in NAION [3] but also can be seen in ON [1-3,10], recovered completely at the time of final examination, whereas visual field defects in NAION rarely recover. Therefore, follow-up visual field tests may aid in the diagnosis of ON.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise for cases of optic neuritis with unaffected visual acuity, peripheral field defects may be present which would get missed on a test such as the microperimetry and would require a full field evaluation. Nevalainen et al, 1 Fang et al 3 , Rothova Z et al, 5 and Mienberg et al 30 agree with this view, but Keltner J et al 4 opine that in most cases, follow-up of optic neuritis eyes can be monitored by central visual field alone.…”
Section: 25mentioning
confidence: 63%
“…Varying patterns of field loss have been reported, ranging from altitudinal, arcuate and centrocaecal to diffuse and even unilateral hemianopic field defects. [1][2][3][4][5][6][7][8] Nearly all studies on visual fields in optic neuritis have been done using the standard automated perimetry, which has inadequate compensation for eye movements and this is particularly important in cases of poor vision and central scotomas such as those seen in optic neuritis. Microperimetry is a novel diagnostic modality that overcomes this limitation by continuously tracking the patient's fundus during stimulus projection.…”
Section: Introductionmentioning
confidence: 99%